2022
DOI: 10.1111/lsq.12379
|View full text |Cite
|
Sign up to set email alerts
|

Who Represents the Constituency? Online Political Communication by Members of Parliament in the German Mixed‐Member Electoral System

Abstract: Members of parliament (MPs) are elected via two different tiers in mixed‐member electoral systems—as winners of a seat in a constituency or as party candidates under proportional rules. While previous research has identified important consequences of this “mandate divide” in parliaments, questions remain how this institutional setup affects MPs' political behavior in other arenas. Analyzing more than one million social media posts, this article investigates regional representation in the online communication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Many countries have "personalized" their electoral systems, allowing voters to express their preferences not only for parties, but also for individual candidates (Renwick and Pilet, 2016). Our findings confirm existing research suggesting that the personalization of electoral systems tends to incentivize candidates to focus on the preferences of their voters (e.g., Zittel et al, 2019;Schürmann and Stier, 2023). Overall, the results emphasize that campaigns function as a crucial democratic mechanism, bridging policy matters between the electoral sphere and the legislative process.…”
Section: Introductionsupporting
confidence: 82%
“…Many countries have "personalized" their electoral systems, allowing voters to express their preferences not only for parties, but also for individual candidates (Renwick and Pilet, 2016). Our findings confirm existing research suggesting that the personalization of electoral systems tends to incentivize candidates to focus on the preferences of their voters (e.g., Zittel et al, 2019;Schürmann and Stier, 2023). Overall, the results emphasize that campaigns function as a crucial democratic mechanism, bridging policy matters between the electoral sphere and the legislative process.…”
Section: Introductionsupporting
confidence: 82%
“…Holding an executive or a parliamentary office likely increases the effectiveness of party discipline (e.g., Zittel and Nyhuis 2019). Second, behavioral differences between MPs elected in the district and on the party list are reported regarding their voting behavior (Sieberer 2010) but also regarding other activities like social media activity (Schürmann and Stier 2022) and MPs' responsiveness to constituency requests (Bol et al 2021). Most of the MPs without party socialization are elected via party list, according to Bailer et al's (2013) data.…”
Section: Methodsmentioning
confidence: 99%
“…Several papers rely on this approach to examine legislators' behavior. (Papp 2021b; Russo 2021a; Schürmann and Stier 2022; Zittel et al 2019). Here I adopt a dictionary that includes the names of all Italian municipalities, regions, national parks, motorways and highways ( autostrade and strade statali ), main rivers and seas 4 .…”
Section: Text Analysis and Geographical Representationmentioning
confidence: 99%
“…Consistent with this view, an extensive body of literature has investigated the consequences of electoral institutions on political representation and MPs' behavior. Research has shown that electoral systems drive a host of behaviors, from representational attitudes to campaign strategies, legislative behavior, and constituency service (Crisp 2007; Heitshusen et al 2005; Proksch and Slapin 2012; Schürmann and Stier 2022; Zittel and Gschwend 2008).…”
mentioning
confidence: 99%